1985
DOI: 10.1128/mcb.5.10.2543
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the mammalian c-fes protein in hematopoietic cells and identification of a distinct fes-related protein.

Abstract: The avian c-fps and mammalian c-fes proto-oncogenes are cognate cellular sequences. Antiserum raised against the P140 ga,-S transforming protein of Fujinami avian sarcoma virus specifically recognized a 92,000-Mr protein in human and mouse hematopoietic cells which was closely related in structure to Snyder-Theilen feline sarcoma virus P87gOg-f's. This polypeptide was apparently the product of the human c-fes gene and was therefore designated p92c-fes. Human p92c-fes was associated with a tyrosine-specific pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 58 publications
9
82
0
Order By: Relevance
“…This excludes p94 fer from being de®ned as an ubiquitous tyrosine kinase. Since the expression of cFes is also restricted to de®ned tissues (MacDonald et al, 1985;Hanazono et al, 1993;Greer et al, 1990Greer et al, , 1994Feldman et al, 1985;Care et al, 1996), this leaves c-Abl as the only known, ubiquitous nuclear tyrosine kinase, which is expressed in all mammalian cells (Wang and Baltimore, 1983;Renshaw et al, 1988;Muller et al, 1982;Boulter and Wagner, 1988;Bernards et al, 1988). The absence of p94 fer from lymphoid progenitor cells and the proven presence of c-Fes in T (Izuhara et al, 1994) and p94 fer in B cell lines, apparently leaves the pre-T and pre-B cells as the only cells, known to harbor c-Abl (Wang and Baltimore, 1983;Renshaw et al, 1988;Ben-Neriah et al, 1986) and not c-Fes or p94 fer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This excludes p94 fer from being de®ned as an ubiquitous tyrosine kinase. Since the expression of cFes is also restricted to de®ned tissues (MacDonald et al, 1985;Hanazono et al, 1993;Greer et al, 1990Greer et al, , 1994Feldman et al, 1985;Care et al, 1996), this leaves c-Abl as the only known, ubiquitous nuclear tyrosine kinase, which is expressed in all mammalian cells (Wang and Baltimore, 1983;Renshaw et al, 1988;Muller et al, 1982;Boulter and Wagner, 1988;Bernards et al, 1988). The absence of p94 fer from lymphoid progenitor cells and the proven presence of c-Fes in T (Izuhara et al, 1994) and p94 fer in B cell lines, apparently leaves the pre-T and pre-B cells as the only cells, known to harbor c-Abl (Wang and Baltimore, 1983;Renshaw et al, 1988;Ben-Neriah et al, 1986) and not c-Fes or p94 fer .…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal tail of p94 fer exerts a coiled-coil structure which mediates the interaction of that kinase with other cellular proteins (Kim and Wang, 1995). Unlike c-Fes whose expression is con®ned to hematopoietic progenitor cells (MacDonald et al, 1985;Care et al, 1996), mature cells of the myeloid lineage (Hanazono et al, 1993;Greer et al, 1990;Feldman et al, 1985;Care et al, 1996) and vascular endothelial cells , p94 fer (Letwin et al, 1988;Hao et al, 1989;Feldman et al, 1986) and c-Abl (Wang and Baltimore, 1983;Van Etten et al, 1989;Renshaw et al, 1988;Muller et al, 1982;Boulter and Wagner, 1988;Bernards et al, 1988) were reported to be ubiquitously expressed in all tissues analysed. Although di ering in their tissue distribution, the subcellular localization of c-Fes and p94 fer is similar and they accumulate both in the cytoplasm and nucleus of the expressing cells (Yates et al, 1995;Hao et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Gag-Fes has an unregulated tyrosine kinase activity that abrogates the need for cytokines in the differentiation of hematopoietic progenitor cells (Carmier & Samarut, 1986;Meckling-Gill et al, 1992). In humans, the expression of Fes was initially detected in myeloid haematopoietic cells (MacDonald et al, 1985;Feldman et al, 1985), where it is believed to participate in the regulation of survival and terminal differentiation. Moreover, Fes is also expressed in vascular endothelial, epithelial and neuronal cells, where it plays an important role in angiogenesis (Greer et al, 1994;Haigh et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In this cell context, Fes is associated with the differentiation process (Feldman et al, 1985;Ferrari et al, 1985Ferrari et al, , 1995Emilia et al, 1986;Yu et al, 1989). In fact, hematopoietic stem cells (Care et al, 1994;Phillips et al, 2000) and leukemic blasts with a differentiation block express low levels of the protein, while more differentiated myeloid cells and leukemic blasts, induced to differentiate by treatment with all trans retinoic acid (ATRA), phorbol esters (PMA) or vitamin D (VD), express higher levels of p92 c-Fes (Ferrari et al, 1985;MacDonald et al, 1985). On the other hand, experiments with antisense oligonucleotides in HL60 cells (M2/M3 type leukemic cells as defined by the FAB and immunophenotypic classification (Bennett et al, 1976;Drexler, 1987)) clearly showed that after inhibition of Fes mRNA and primary transcript, the mono-machrophagic differentiation induced by treatment with PMA is no longer achievable .…”
Section: Introductionmentioning
confidence: 99%